A imunidade impositiva das instituições de educação e de assistência social, sem fins lucrativos: abrangência dos impostos indiretos - Franco, Patrícia Neves (2021)
The impact of excise taxes, the so-called indirect taxes, on the daily lives of Brazilian citizens, in particular the ICMS (tax on distribution of goods and services – equivalent to sales taxes) and the IPI (tax on manufactured products), is notorious, which encumber the most diverse goods available to meet human needs and end up generating unavoidable effects that reduce portion of the taxpayers' equity. In this case, the economic effects are assumed by the actual taxpayers, end consumers in the production chain, considering the vocation of these taxes to the occurrence of the phenomenon of economic translation. When facing an end consumer who can occupy the taxpayer’s position (in fact or in law), there is no question to be asked, as the economic repercussion is inherent to such taxes, including by constitutional provision. However, when the end consumer is a legal entity that takes advantage of immunity, we need to look into the matter to assess whether or not the assumption of responsibility by such institutions is constitutional. The immunities granted to educational and social assistance institutions, with no profit purpose, are based on the protection of the purposes pursued by such entities, which have a social character and replace the State in the performance of public services that it should, but which are provided by legal entities governed by private law, by virtue of the delegation, considering the impossibility of the state apparatus to meet all the demands of society. Thus, such immunities ensure that no portion of the assets of these entities is transferred to the public coffers, allowing the entire set of assets and income obtained by them to be destined to the execution of their essential purposes, resulting in gains for the entire society. In this context, the present work aims to study whether the immunity in question covers, besides the direct taxes, indirect taxes (ICMS and IPI), when these immune entities occupy the condition of end consumer. Therefore, the opinions of the doctrine that was dedicated to the subject will be analyzed, as well as the jurisprudence of the Federal Supreme Court on the matter